2013
DOI: 10.1111/eos.12048
|View full text |Cite
|
Sign up to set email alerts
|

Novel RUNX2 frameshift mutations in Chinese patients with cleidocranial dysplasia

Abstract: Cleidocranial dysplasia (CCD) is a skeletal disorder caused by heterozygous mutations in the runt-related transcription factor 2 (RUNX2) gene. We evaluated the phenotypes of eight Chinese patients with CCD from three unrelated families followed by analysis of the RUNX2 genes. Three different RUNX2 frameshift mutations were identified. Two of the mutations are novel (c.887insC and c.592delA) and one (c.90insC) has been described previously. Surprisingly, the patient with the most severely truncated RUNX2 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Majority of RUNX2 mutations in individuals suffering from classic CCD occur in the runt domain and the most common DNA disruptions are missense mutations that prevent RUNX2 binding to DNA or nonsense mutations that result in biosynthesis of truncated protein. While missense mutations are uniquely found within runt‐domain region, nonsense and frame‐shift types were described throughout the gene (Fig. , Table ).…”
Section: Mutations In Human Runx2mentioning
confidence: 99%
“…Majority of RUNX2 mutations in individuals suffering from classic CCD occur in the runt domain and the most common DNA disruptions are missense mutations that prevent RUNX2 binding to DNA or nonsense mutations that result in biosynthesis of truncated protein. While missense mutations are uniquely found within runt‐domain region, nonsense and frame‐shift types were described throughout the gene (Fig. , Table ).…”
Section: Mutations In Human Runx2mentioning
confidence: 99%
“…Another reason why the mutations might result in decreased transcriptional activity of RUNX2 could be impaired transport of the protein to the cell's nucleus. It has been previously shown that RUNX2 contains a Nuclear Localization Signal (NLS) downstream of the Runt domain (PRRHRQKLD) that, when defective, causes the accumulation of RUNX2 in the cytoplasm . Since one of the identified mutations, Δe4 c.580+1G>T (IVS3+1G > T), resulted in the absence of 35 aa spanning the Runt domain and a part of NLS (Figure ), we tested the effect of that mutation on the nuclear translocation of RUNX2.…”
Section: Resultsmentioning
confidence: 99%
“…Although there have been numerous genetic studies about CCD in Asian populations, there are only three case reports or genetic studies of Korean CCD patients . Kim et al identified four novel Runx2 mutations in 11 Korean CCD patients (Q50X, E112X, R131G in exon 2, and an exon 1 slice donor site mutation).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Until now, more than 80 mutations in Runx2 gene have been identified, 7 most of which are missense mutations in the Runt domain. 8 Although there have been numerous genetic studies about CCD in Asian populations, [9][10][11][12][13][14][15][16] there are only three case reports or genetic studies of Korean CCD patients. 2,17,18 Kim et al 2 identified four novel Runx2 mutations in 11 Korean CCD patients (Q50X, E112X, R131G in exon 2, and an exon 1 slice donor site mutation).…”
mentioning
confidence: 99%